Kemiskinan Struktural dalam Novel Dompet Ayah Sepatu Ibu karya J. S. Khairen - Veronica, Nia; Adek, Muhammad (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to provide a comprehensive analysis of the forms, causes, and impact of structural poverty in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen. Drawing on the principles of literary sociology theory, a descriptive method is employed, utilizing content analysis techniques. Through data analysis, five distinct forms of structural poverty are identified: limited access to education, inadequate healthcare services, lack of sanitation and clean water, limited job opportunities and unfair wages, and insufficient social welfare support. The factors contributing to poverty are categorized as either individual or government-related. Moreover, the impact of structural poverty is classified into three distinct categories: legal, moral, and social consequences.